ANALISIS HIPERTENSI BERDASARKAN PEMERIKSAAN KESEHATAN PADA JAMAAH HAJI KABUPATEN BANYUMAS - Khusnul Khotimah; Heriyanto Heriyanto; Yuli Trisnawati (Ensiklopedia of Journal, 2026)
A significant risk factor for death, hypertension is a condition that many Indonesian Hajj pilgrims suffer from. Among the top 5 conditions among Hajj pilgrims in Banyumas Regency, hypertension is the most common (42.19% in 2022 and 38.60% in 2023). This study aimed to determine the factors linked to hypertension among Hajj pilgrims in Banyumas Regency. This study is a cross-sectional analytical epidemiology. The 1,228 The study's population consisted of Banyumas Regency Hajj pilgrims who departed in 2023. The technique used was total sampling. The phases of data analysis included univariate analysis, bivariate analysis using the Chi-square test, and multivariate analysis using the logistic regression test. The results of the study indicate that age (P value = 0.0001; POR = 4.065), obesity (P value = 0.0001; POR = 3.089), and a family history of hypertension (P value = 0.0001; POR = 5.226) are factors associated with hypertension among Banyumas Regency Hajj pilgrims. Gender and smoking behaviors are unrelated issues. Prospective Hajj pilgrims can prevent and control risk factors for hypertension by engaging in regular physical exercise, making dietary improvements, and getting regular checkups until they travel for the Hajj.Keywords: Risk Factors, Hajj Pilgrims, Hypertension